ANALISIS KESIAPAN TRANSFORMASI DIGITAL PADA KELURAHAN PALEMBANG - Julizar, Salshabila Pratami Putri; Antoni, Darius; Faradillah (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Digital transformation is an important process to improve the efficiency and quality of services, including within the scope of village government. This study aims to analyze the extent to which Palembang Village is ready to face digital transformation by assessing factors such as environment, strategy, organization, human resources, service offerings, and technology and innovation. The methodology used is quantitative through surveys, questionnaires, and linear regression analysis. The findings of this study indicate that organization and human resources are the most significant factors influencing digitalization readiness. Validity and reliability testing show a high level of consistency in the research measuring instruments used. This study recommends increasing training for the workforce, strengthening technology infrastructure, and integrating digital systems to accelerate the digital transformation process. With the implementation of a planned digital transformation, it is hoped that there will be an increase in operational efficiency and public satisfaction with village services.